2002
DOI: 10.1080/10242690210973
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Turkish Defence Expenditure

Abstract: Although a number of studies concerning Turkish defence-growth relation have been published in recent years, little attention is given the demand for Turkish defence expenditure. This is an important issue for understanding which variables contribute to the determination of the demand for military expenditure. However, it is difficult to develop a general theory or a standard empirical approach for the determination of the demand military expenditure. This study models and estimates the demand for Turkish defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 8 publications
1
33
0
2
Order By: Relevance
“…As argued by Sezgin and Yildirm (2002), that ARDL can be applied regardless of stationary properties of variables in the sample and allows for inferences on long run estimates, which is not possible under alternative co-integration techniques. In contrast, according to Ouattara (2004) in the presence of I(2) variables, the computed F-statistics provided by PSS (2001) become invalid because the bounds test is based on the assumption that the variables should be I(0) or I(1).…”
Section: Empirical Interpretationsmentioning
confidence: 97%
“…As argued by Sezgin and Yildirm (2002), that ARDL can be applied regardless of stationary properties of variables in the sample and allows for inferences on long run estimates, which is not possible under alternative co-integration techniques. In contrast, according to Ouattara (2004) in the presence of I(2) variables, the computed F-statistics provided by PSS (2001) become invalid because the bounds test is based on the assumption that the variables should be I(0) or I(1).…”
Section: Empirical Interpretationsmentioning
confidence: 97%
“…Brauer (2002) notes that the results obtained appear to depend on whether level or share data are used. Following Smith (1989Smith ( , 1990 and Sezgin and Yildirim (2002), all military expenditure series used in both models are expressed as shares of GDP. In Model 1, defence is treated as a public good and the share of defence spending (MG) should be positively related to income because higher income levels tend to generate higher defence spending.…”
Section: Determinants Of Greek Defence Expenditurementioning
confidence: 99%
“…Selami and Yildirim (2002) examined the demand for Turkish defence expenditure for the period 1949-1998. They found that there is a mixed result.…”
Section: Literature Reviewmentioning
confidence: 99%